The little adobo book - Gonzalez, Gene (Pasig, Philippines: Anvil Publishing, 1999)
This first book in the series shows the ease of method and preparations for Philippine adobo, a simple dish that transcends gastronomic incompatibilities between Philippine regions and ethnic groups, each having their own versions of this cooking method plus its appeal to foreign visitors who find this dishes representative of true tropical cuisine .
Basic Philippine adobo -- Adobong crispy pata -- Adobong bibe -- Kinunot na pagi -- Sinaing na tambakol sa bawang at kamatis -- Adobong pusit sa saging -- Adobong paa ng manok sa gata -- Adobong sili -- Arobong camaru -- Binagoongang baboy -- Adobong tsino -- Apalit adobo -- Adobong tugak quing dilo -- Chicken adobo with coco cream -- Adobong pang inuman -- Batangas beef adobo -- Chicken pork adobo -- Spicy chicken adobo -- Bringhe -- Adobo mushroom -- Adobong pusit sa tinta -- Pininyahang adobo -- Adobong kangkong -- Sisig lechon -- Kilawin or adobong labanos -- LAgat na kanduli sa dilaw -- Sisig pusong saging -- Adobo de campesino -- Bopis -- Adobo flakes -- Adobo mates .
Keywords: FILIPINO CUISINE; ADOBO RECIPE